TOWARDS A RECOGNITION OF THE PLURALITY OF KNOWLEDGE IN SOCIAL WORK: The Indigenous Research Paradigm - Ellington, Lisa (Canadian Social Work Review / Revue canadienne de service social, 2019)
Social work as a profession has undergone significant change in recent decades, modulated by the various social, political, and organizational transformations of the society in which it evolves. Today, there is increasingly diversified research encompassing a number of coexisting visions of social work. These multiple visions come hand in hand with values, principles, as well as ideologies, some of which are dominant, and others that are marginal. Indigenous Peoples are among the most marginalized groups in society and so are Indigenous worldviews within the profession. Currently, there seems to be a willingness to recognize the plurality of knowledge in the area of social work. In line with this objective, the purpose of this article is to present the Indigenous research paradigm. This is a theoretical contemplation centered around the historical context that led to the paradigm’s creation, a description of what it consists of, as well as a presentation of a few examples of its use by social work researchers. Finally, the paper brings up certain persistent issues related to the recognition of the Indigenous paradigm within the profession.